Evaluation of cardiac insult in steers with different dietary sodic monensin concentration measured thought miocardic kreatin kinaza (Veterinary Science, 2017)
The aim of this study was to evaluate a possible myocardial  damage on feedlot steers caused by high doses of monensin (MN). A commercial kit was used to determinate the concentration of myocardial creatine kinase (CK-MB). Four groups of animals were conformed according to the diet MN concentration. G1: Control, without MN, G2: MN Tag dose, 1 mg kg body weight (BW) -1 , G3: MN 5 mg kg BW -1 and G4: MN 10 mg kg BW -1 The cattle were housed in pens for eleven days. Venous blood  samples were taken at 0, 48, 120, 168 and 264 h. Serum CK-MB  concentration was analyzed using descriptive and comparative  statistics analysis of variance (ANOVA) with a significance level  of P
Keywords: feedlot health; monensina; myocardial creatine ki - nase; cardiac damage